The effect of crocin and losartan on TGF-β gene expression and histopathology of kidney tissue in a rat model of diabetic nephropathy - Yaser Mohammadi; Mohammad Zangooei; Mahmoud Zardast; Morteza Mamashli; Azam Rezaei Farimani (Mashhad University of Medical Sciences, 2023)
Objective: Diabetic nephropathy is one of the most common microvascular complications of diabetes mellitus that finally leads to complete loss of kidney function. Therefore, this study aimed to evaluate the effect of crocin and losartan on TGF-β gene expression and histopathology of kidney tissue in a rat model of diabetic nephropathy.Materials and Methods: Forty male Wistar rats were randomly divided into five groups (n=8): Untreated control, Diabetic (D), D + crocin, D + losartan, and D + losartan + crocin. Induction of diabetes was performed using streptozotocin (50 mg/kg/ Intraperitoneal injection). At the end of the eight-week period, the rats were sacrificed. Spectrophotometry measured serum glucose, urea, creatinine, and uric acid levels. Microalbumin and creatinine levels were measured in 24-hour urine. Real-time PCR was used to determine the relative expression of the TGF-β gene in kidney tissue. Renal tissue histopathology was also examined.Results: The results showed that hyperglycemia increased biochemical factors associated with diabetes, TGF-β gene expression, and kidney damage. Separate treatment with crocin and losartan led to a decrease in renal function factors and TGF-β gene expression and improved kidney damage.Conclusion: Our results showed that crocin could improve kidney function in diabetic conditions. In addition, we showed that crocin increases the effectiveness of losartan. Consequently, we suggest that crocin in combination with chemical drugs can be a potential therapeutic agent for diabetes and its complications. Nonetheless, human studies are needed to make firm findings.